Effects of arbuscular mycorrhizal inoculation and fertilizer on production of Castanopsis acuminatissima saplings for forest restoration in northern Thailand - Nandakwang P. (2014)
Castanopsis acuminatissima is a native tree used to restore forest in Thailand. To accelerate seedling growth experiments were carried out to determine the efficacy of applying to C. acuminatissima. Arbuscular Mycorrhizal (AM) fungi, produced on sorghum, were used as inoculum to investigate the symbiosis on seedlings. The effects of AM inoculation (Acaulospora elegans, Glomus etunicatum, Glomus mosseae) together with phosphate fertilization (KH2PO4) on seedlings in a P-deftcient soil were studied under greenhouse conditions. Increasing P-application rates greatly enhanced seedling growth (maximum at 250 mg kg-1 soil). Growth was most rapid with G. etunicatum-colonized plants with P application (40.8 cm), whereas much lower height was found with non-AM plants without P added (14.4 cm). The mycorrhizal effective for C. acuminatissima in previous experiments were confirmed by growing seedlings in a forest soil with slow-release fertilizer (NPK) and combined with AM species under nursery performance conditions. Plant height was significantly enhanced by fertilizer but not by fungi. The greatest height was found in non-AM plants with fertilization (14.5 cm), whereas lower height was found for non-AM plants with no fertilizer added (10.9 cm). AM inoculation greatly enhanced seedling growth in P-deficient soil more than in forest soil due to differences in abilities of AM species to establish a symbiosis. Therefore, in sapling production, the soil properties and level of fertilization should be evaluated keeping secondary effects caused by changed mycorrhizal association. © 2008 Academic Journals Inc.